American Foreign Policy towards Iraq, Iran and North Korea: American Hegemony and Neo-conservatism against the Axis of Evil - Seniwati Ismail (Departemen Ilmu Hubungan Internasional Univesitas Hasanuddin, 2015)
AbstractThis article analyzes the United States toward “axis of evil” countries, namely Iraq, Iran and North Korea. Since September 11, 2001, according to George Walker Bush, these countries are sponsor of terror that threat America or friend’s and allies’ of America with weapons of mass destruction.